Implementasi Quadruple Helix sebagai Upaya Peningkatan Pembelajaran di SMP 28 Desa Tanjung, Kecamatan Rusip Antara, Kabupaten Aceh Tengah - Arafah, Yunita; Aditya, Atika; Fakhrana, Siti Zahrina (Universitas Syiah Kuala, 2025)
This community service program aims to enhance the quality of education at SMP 28, located in Tanjung Village, Rusip Antara Subdistrict, Central Aceh Regency, by strengthening digital learning infrastructure by implementing the Quadruple Helix approach. This model promotes collaboration among four key sectors: academia, community, industry, and government. The initiative involved active participation from the Faculty of Engineering at Universitas Syiah Kuala (academia), the Aceh branch of the Indonesian Big Motorcycle Association (IMBI) and Forum Mahasiswa Aceh Dunia (FORMAD) (community), Aceh Link (private sector), as well as SMP 28 and the District Education Office of Central Aceh (government). The scope of activities included the procurement of 15 uninterruptible power supply (UPS) units for school computers, upgrading and restructuring of the computer network and local area network (LAN), conversion of the schools electricity system from prepaid to postpaid, installation of internet access using Starlink satellite technology, deployment of multiple access points to ensure wide-area internet coverage, enhancement of electrical capacity, and normalization of the electrical installation system. The outcomes indicate that the integrated contribution of all stakeholders under the Quadruple Helix framework was instrumental in overcoming infrastructure challenges schools face in remote areas. As a result, the school is now better equipped to support digital-based learning and ensure sustainable access to online educational resources, thereby improving the overall teaching and learning experience.